THE DISTRIBUTION MODELS ADEQUACY ESTIMATION FOR USING IN SUBSCRIBER LOCATION DETERMINATION - Ткаліч, О.П.; Одарченко, Р.С.; Устинов, О.Ю.; Колодинський, Д.О. (Science-based technologies, 2015)
In corporate networks with a large number of subscribers it is an important aspect to provide quality and timely service to provide information services and monitoring the movement of subscribers within the network. To solve this problem it is necessary to provide location determination. The article describes the method of position determining of the subscriber by measuring the radio signal strength at the mobile station. The article analyzes the existing empirical distribution models that operate in a given frequency range. An experimental research of the signal power measurement for a variety of determination conditions, namely indoor and outdoor space. Verification of empirical model with experimental data was made. The optimal model was defined for calculating the subscriber location for indoor and outdoor space.